Pola Pembinaan Keimanan dan Ketakwaan Siswa di SMK Negeri Kencong Kabupaten Jember: Patterns of Faith and Piety Development Among Students at Kencong State Vocational High School, Jember Regency - St. Mislikhah (Fenomena, 2005)
Fostering faith and piety (imtak) as the core of Indonesia’s national education goals faces persistent challenges, including dichotomous views of religious and general knowledge, limited teacher competence, and suboptimal collaboration among schools, parents, and the community. This qualitative descriptive study, framed by the theory of integrative imtak development and the national education system as a holistic entity, describes patterns of imtak development at SMAN 1 Kencong. Data were collected through observation, interviews, questionnaires, and documentation from purposively sampled teachers, then analyzed using an interactive model. The findings reveal that imtak development is implemented through five integrated strategies: optimizing Islamic Religious Education instruction with varied methods and functional material delivery; integrating imtak values into general/science subjects, practiced by 85% of teachers; structuring religious extracurricular activities such as Ramadan programs, Quran recitation, and qurban; creating a conducive Islamic school climate through salam, doa, infaq, and congregational prayers; and establishing collaborative partnerships with parents and the community for both preventive and curative interventions. The study concludes that a holistic, multi-strategy pattern effectively enhances students’ religious commitment, discipline, and moral conduct, and recommends systematic teacher training and formalized school-community cooperation mechanisms. Urgensi pembinaan keimanan dan ketakwaan (imtak) sebagai inti tujuan Pendidikan Nasional Indonesia menghadapi tantangan seperti pandangan dikotomis antara ilmu agama dan umum, keterbatasan kompetensi guru, serta belum optimalnya kerja sama sekolah dengan orang tua dan masyarakat. Penelitian deskriptif kualitatif ini, yang berlandaskan pada teori pembinaan imtak integratif dan sistem pendidikan nasional sebagai kesatuan utuh, bertujuan mendeskripsikan pola pembinaan imtak siswa di SMAN 1 Kencong. Data dikumpulkan melalui observasi, wawancara, angket, dan dokumentasi dari guru yang dipilih secara purposive, lalu dianalisis dengan model interaktif. Temuan penelitian menunjukkan bahwa pembinaan imtak dilakukan melalui lima strategi terpadu: optimalisasi Pendidikan Agama Islam dengan metode bervariasi dan materi fungsional; integrasi nilai imtak ke mata pelajaran umum/iptek yang dilakukan 85% guru; kegiatan ekstrakurikuler keagamaan seperti Ramadhan, tadarus, dan kurban; penciptaan iklim sekolah Islami melalui salam, doa, infak, dan salat berjamaah; serta kerja sama dengan orang tua dan masyarakat untuk tindakan preventif dan kuratif. Penelitian menyimpulkan bahwa pola holistik multi-strategi efektif meningkatkan komitmen beragama, disiplin, dan akhlak siswa, dengan rekomendasi pelatihan guru sistematis dan formalisasi kerja sama sekolah-komunitas.